(untitled) (Annals of Medical Research, 2023)
Aim: The aim of this study was to determine how local dexmedetomidine and sugammadex application affect TNF- α IL-1β levels, and histopathological scores, which are important markers of inflammatory response, in a rat experimental wound model. Materials and Methods: In Group D, 2 ml of 10 mcg diluted dexmedetomidine (n=8), 2 ml of 10 mg diluted sugammadex (n=8), and 2 ml of saline (n=8) were infiltrated into the incision lips. Plasma TNF-α, IL1-β levels was measured. The rats were awakened. Their survival was continued for 7 days. On the seventh day following the procedure, a biopsy was taken from the subjects’ incision line, and their histopathological wound healing scores were evaluated. Results: There was a difference between the mean values of TNF-α between the groups (p=0.016). TNF-α was found to have a mean value of 299.59 in the control group, 253.41 in the dexmedetomidine group, and 249.51 in the sugammadex group. IL-1β values, chronic inflammation (CI), granulation (G) and fibrosis (F) scores did not differ between groups (p values ​​0.752, 0.118, 0.368, and 0.296, respectively). The active inflammation (AI) scores of the all groups differed significantly (p=0.007). Conclusion: Dexmedetomidine and sugammadex have been shown to accelerate the migration of polymorphous core leukocytes to the wound site. We believe that our research will shed light for future clinical trials.